Gender disparities in the pediatric allergy‐related guidelines in Japan. Issue 1 (12th March 2022) - Inage, Eisuke; Tanaka, Yuko; Matsui, Kotoko; Yamada, Hiromichi; Kojima, Mayuki; Toriumi, Shun; Kudo, Takahiro; Baba, Yosuke; Shimizu, Toshiaki
Abstract: Background: Inclusion of female authors has been noted as potentially beneficial in the development of medical guidelines. Japanese professional committees representing allergic subspecialties develop practical guidelines with recommendations to caregivers, but these committees may be influenced by their gender composition. The objective of our study was to examine the influence of gender in developing pediatric allergic disease guidelines in Japan from 1999 to 2020. Methods: We examined the gender parities among the guideline committee members in allergic rhinitis, atopic dermatitis, bronchial asthma, and food allergy guidelines in Japan. We examined the gender composition of the committees, annual trends, and differences in guideline content. Results: The median proportion of women members among the 22 guidelines committees was 6.6% (range: 0%–27.3%). The analysis of the quadrant period did not show a significant increase in the proportion of female members. The food allergy group had a significantly higher proportion of female members than other guidelines ( P < 0.01), but the proportion decreased from 25% to 14.3% during the observation period. For the pediatric asthma guidelines, the proportion of female committee members decreased from 5.3% in the 2000 version to 0% in the most recent revision in 2017. Conclusions: The proportion of women on the committees that develop pediatric guidelines continues to be low and has not improved over the past 20 years.